2018
DOI: 10.3390/educsci8020088
|View full text |Cite
|
Sign up to set email alerts
|

To Understand the “Brazilian Way” of School Management: How National Culture Influences the Organizational Culture and School Leadership

Abstract: Abstract:This study aims to identify characteristics of national culture in the culture of Brazilian school management and leadership. Considering the broad literature that deals with the peculiarities of Brazilian culture and its influence on Brazilian management, it is assumed that as an institution belonging to a particular society, the school offers internal dynamics that are organized under influences of historical and cultural determinants of this society. This work is an exploratory study that uses seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Are these beliefs about teachers' qualities influenced by national norms and traditions? Many scholars of school leaders agree that cultures shape organizational practices and leadership behaviors (Hofstede et al, 2010;de Albuquerque Moreira & Rocha, 2018;Dimmock & Walker, 1999;Miller, 2018;Spencer-Oatey, 2000;Shapira-Lishchinsky & Litchka, 2018). Cultures from the context in which schools run and, also, shape how school principals think and act (Dimmock & Walker, 2002, p.70).…”
Section: B the Influence Of Culture On School Leadership Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Are these beliefs about teachers' qualities influenced by national norms and traditions? Many scholars of school leaders agree that cultures shape organizational practices and leadership behaviors (Hofstede et al, 2010;de Albuquerque Moreira & Rocha, 2018;Dimmock & Walker, 1999;Miller, 2018;Spencer-Oatey, 2000;Shapira-Lishchinsky & Litchka, 2018). Cultures from the context in which schools run and, also, shape how school principals think and act (Dimmock & Walker, 2002, p.70).…”
Section: B the Influence Of Culture On School Leadership Practicesmentioning
confidence: 99%
“…Some research highlighted the influence of cultural background on school leadership. In a recent study about the role of Brazilian national culture on school leadership, de Albuquerque Moreira and Rocha (2018) showed that the high distance power of Brazilian culture is reflected in school organizational management and leadership as high centralization and reduced autonomy of schools. The authors emphasized that many aspects of national culture such as authoritarianism, personalism, patriarchy, paternalism, hierarchy, the mix between the public and private spheres, and cordiality, result from the historical process of colonization and constitute a consequence of the intercultural contact between three main cultures: Iberian, Amerindian, and African.…”
Section: B the Influence Of Culture On School Leadership Practicesmentioning
confidence: 99%